Endoscopic wire‐guided papillectomy versus conventional papillectomy for ampullary tumors: A prospective comparative pilot study. Issue 4 (April 2016) - Lee, Tae Yoon; Cheon, Young Koog; Shim, Chan Sup; Choi, Hyun Jong; Moon, Jong Ho; Choi, Jung Sik; Oh, Hyoung‐Chul
Abstract: Background and Aim: A major concern about endoscopic snare papillectomy (ESP) is the risk of procedure‐related pancreatitis. To maintain pancreatic duct access for stent placement after ESP, wire‐guided ESP (WP) was introduced. The aim of the study was to compare post‐procedure pancreatitis rates, the success rate of pancreatic stent insertion, and complete resection rates between WP and conventional ESP (CP) procedures. Methods: This was a multi‐center, prospective, randomized pilot study. Forty‐five patients with ampullary tumors were randomly assigned to a WP group ( n  = 22) or a CP group ( n  = 23). In the WP group, a guidewire was placed in the pancreatic duct prior to ESP. A 5‐Fr pancreatic stent was passed over the guidewire and placed across the pancreatic duct orifice. Results: Complete resection was achieved in 20 patients (91%) in the WP group and 18 patients (78%) in the CP group ( P  = 0.414). A pancreatic stent was placed successfully in all patients in the WP group but in only 15 patients (65%) in the CP group ( P  = 0.004). Post‐papillectomy pancreatitis occurred in four (18%) patients in the WP and three (13%) patients in the CP groups ( P  = 0.960). In the CP group, three of eight (37.5%) patients without stents developed pancreatitis compared with zero of 15 patients with stents ( P  = 0.032). Conclusions: The WP method is a useful technique used to insert a pancreatic stent after ESP, compared with CP. However, there was no significant difference in the post‐procedure pancreatitis or complete resection rates between the two methods.